2022
DOI: 10.3390/jcm11030721
|View full text |Cite
|
Sign up to set email alerts
|

Changing Metabolic Patterns along the Colorectal Adenoma–Carcinoma Sequence

Abstract: Colorectal cancer (CRC) is a major public health burden and one of the leading causes of cancer-related deaths worldwide. Screening programs facilitate early diagnosis and can help to reduce poor outcomes. Serum metabolomics can extract vital molecular information that may increase the sensitivity and specificity of colonoscopy in combination with histopathological examination. The present study identifies serum metabolite patterns of treatment-naïve patients, diagnosed with either advanced adenoma (AA) or CRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…LC-MS-based serum profiles showed saturated TAG as the main perturbed lipids in CRC progression and the authors pointed towards LD accumulation as the origin [ 102 ]. Another group observed decreased levels of lyso-lipids, glycophosphocholines and acylcarnitines serum concentrations in CRC patients [ 103 ]. Very recently, Ecker et al additionally identified a robust TG lipidomic tissue signature that could discriminate patients and was proposed as prognostic identifier.…”
Section: Colorectal Cancer Lipidomementioning
confidence: 99%
“…LC-MS-based serum profiles showed saturated TAG as the main perturbed lipids in CRC progression and the authors pointed towards LD accumulation as the origin [ 102 ]. Another group observed decreased levels of lyso-lipids, glycophosphocholines and acylcarnitines serum concentrations in CRC patients [ 103 ]. Very recently, Ecker et al additionally identified a robust TG lipidomic tissue signature that could discriminate patients and was proposed as prognostic identifier.…”
Section: Colorectal Cancer Lipidomementioning
confidence: 99%
“…14 In addition, holistic changes in the metabolic pathways have been reported, including amino acid, pentose phosphate, urea cycle, polyamine, and nucleotide pathways. [15][16][17] Therefore, the metabolites in biofluids including blood and saliva that reflect these metabolic aberrances associated with CRC have been analyzed to establish a novel set of biomarkers. [18][19][20][21][22][23][24] Saliva is an ideal biofluid that enables various disease detections.…”
Section: Introductionmentioning
confidence: 99%
“…Glutamine is used as a carbon source alternative to glucose via the TCA in proliferating tumor cells to synthesize purines and pyrimidines 14 . In addition, holistic changes in the metabolic pathways have been reported, including amino acid, pentose phosphate, urea cycle, polyamine, and nucleotide pathways 15–17 . Therefore, the metabolites in biofluids including blood and saliva that reflect these metabolic aberrances associated with CRC have been analyzed to establish a novel set of biomarkers 18–24 …”
Section: Introductionmentioning
confidence: 99%
“…Lipid species are widely distributed and important endogenous substances in vivo that have been demonstrated to be involved in the occurrence and development of various tumors ( 17 , 18 ). Recent studies have reported that perturbation of lipid metabolism is closely related to the progression of CRC ( 19 , 20 ). The lipid metabolic pathways in CRC cells are affected, including fatty acid synthesis, desaturation, elongation, and mitochondrial oxidation ( 21 ).…”
Section: Introductionmentioning
confidence: 99%